Uji Efektifitas Jamur Entomopatogen Beauveria bassiana (Bals.) dan Metarrhizium anisopliae (Metch) terhadap Chilo sacchariphagus Boj. (Lepidoptera : Pyralidae) di Laboratorium - Nova Berta Sianturi; Yuswani Pangestiningsih; Lahmuddin Lubis (Jurnal Agroekoteknologi, 2014)
The objective of this research was to know the effectivity of entomopathogenic fungi B. bassianadan M. anisopliae to C. sacchariphagus with different concentration levels. This research wasconducted at the Laboratory of Pest, Agroecotechnology Program Study, Faculty of Agriculture,University of North Sumatera, with altitude ±25 m asl from February until March 2014. Themethod used Randomized Completely Design non factorial which consist of 7 treatments and 3replication. The treatments consist of : T0 (Control), T1(B. bassiana 30gr/1l water), T2 (B. bassiana40gr/1l water), T3 (B.bassiana 50 gr/1l water), T4 (M. anisopliae 30gr/1l water), T5 (M. anisopliae40gr/1l water), T6 (M. anisopliae 50gr/1l water). Parameters measured were percentage mortalitylarva and the change of morphology larva. The result showed that the most effective B. bassiana isthe treatment T2 dan T3 by 73.33% and 86.67% and the most effective M. anisopliae is thetreatment of T5 dan T6 by 86.67% and 100.00%. The observation of the change of morphology oflarva C. sacchariphagus was as the following: the movement of larva C. sacchariphagus becameslow (lazy), the body of the larva was weakening dead and hardening, and finally was covered bydifferent colors of mycelium, i.e. B. bassiana was covered by and mycelium white M. anisopliaewas covered by green mycelium.Key words: Beauveria bassiana, Chilo sacchariphagus, Metarrhizium anisopliae, sugar cane